Respuestas

2014-02-27T04:59:37+01:00
A) 3(2x + 5) - 2(4 + 4x)=7

6x + 15 - 8 - 8x = 7
2x + 7 = 7
2x = 0
x = 0




b) 4- x+3 = 2+ 9-2x
         6            3
Multiplica la ecuación por 6.

24 - x + 3 = 12 + 18 - 4x
-x + 27 = 30 - 4x
3x = 3
x = 1

c) 4(3x + 6)  + 3 = 2(2x + 5) - 3x
        5                        3
Multiplica por 15 ( mmc).

12(3x + 6) + 45 = 10(2x+5) - 45x
36x + 72 + 45 = 20x + 50 - 45x
36x + 117 = -25x + 50
61x = -67
x = -67/61

sl2 avisas cualquier duda
muchas gracias te lo agradezco tantoo
;)